A associação em redes de cooperação influencia os resultados de pequenas e médias empresas? - Jorge Verschoore; Alsones Balestrin (Ciências Sociais Unisinos)
The association in small fi rm networks has been a decision taken by small and mid-sized companies in order to obtain the gains provided to their members. Several studies have already shown the outcomes obtained by network cooperation, but few managed to verify if such outcomes affect positively the results of the companies that take part of the networks. The main objective of this article is to identify whether the participation in small fi rm networks infl uence the results of associated companies. A quantitative research has been conducted on a sample of 816 businesses associated to the cooperation networks formed by a public policy developed by the Government of Rio Grande do Sul State. The results of the survey indicated an increase of 23.64% on company¿s revenues after the association with a network. The results also showed that the perception of gains of associated companies is amplifi ed as there is an increase in the number of members and the network grows older. Based on the data, in-depth analyses on the different results achieved by companies linked to the networks were performed.